O direito à educação e a educação em/para direitos humanos no PNDH-3 - Pessoa, Ana Carolina Pedrosa Ribeiro (2011)
Education, besides being a human right, is also a fundamental tool for the realization of other rights. Based on this understanding, the object of this study is Human Rights Education understood now as a set of processes of formal and non-formal education, focusing on building a culture of respect for human dignity. The paper presents the rationale and conceptualization of HRE from international human rights law and makes a historical approach to human rights education in Brazil since the 1988 Constitution until the publication of the third version of the National Human Rights Program in 2009, demonstrating the development of the process of institutionalization of the subject as public policy in the country. The main objective of this essay is to examine the contents of PNDH-3 with a focus on HRE. To this end, there was a work of mapping, surveying and systematizing the actions related to education as a human right to education on human rights (by establishing a parallel with the National Plan for Human Rights Education - PNEDH) and education for human rights that cuts across the whole program and is seen as a tool for achieving public policy in several areas. The strategic actions related to HRE contained in six guiding axes of the document were listed in categories and systematized by frame, allowing the reader to visualize the recognition of the institutional and social issue and its importance and contribution to sustain the promotion, protection and human rights, and redress of violations.